5-Hydroxytryptamine1A receptor binding activity of bisbenzyltetrahydroisoquinoline alkaloids from Popowia odoardi - Chung, L.Y.; Soo, W.K.; Mustafa, Mohd Rais; Goh, S.H.; Imiyabir, Z. (Taylor & Francis, 2009)
A 96-well filtration-based 5-HT1A receptor-radioligand binding assay was optimized and adapted to carry out a bioassay-guided fractionation of the methanol extract of the bark of Popowia odoardi Diels(Annonaceae). This purification led to the isolation of two compounds identified as O-methyldauricine (1)and popisidine (2), which bind competitively to 5-HT 1A receptors at high concentrations with K ivalues of 4.5 and 5.8 μM, with [ 3 H]8-OH-DPAT as the radioligand. These results suggest that both of these bisbenzyltetrahydroisoquinoline alkaloids influence the activity of 5-HT 1A receptors through competitive binding as agonists or antagonists and may possess anxiolytic and anti-depressive effects.